Re-writing international relations history and theory beyond Eurocentrism in Turkey - Çapan, Zeynep Gülşah (Rowman & Littlefield, 2016)
This book tells a different story of International Relations by challenging disciplinary and theoretical boundaries from the Turkish perspective with the aim of creating a more connected and global International relations
Includes bibliographical references and index
Keywords: Internationale Politik; International relations; Eurocentrism; Historiography; Geschichtsschreibung; Eurozentrismus; Türkei